Gadd45 in the response of hematopoietic cells to genotoxic stress - Liebermann, Dan A (2007)
Gadd45 genes have been implicated in stress signaling in response to physiological or environmental stressors, which results in either cell cycle arrest, DNA repair, cell survival and senescence, or apoptosis. Evidence accumulated implies that Gadd45 proteins function as stress sensors is mediated by a complex interplay of physical interactions with other cellular proteins that are implicated in cell cycle regulation and the response of cells to stress. These include PCNA, p21, cdc2/cyclinB1, and the p38 and JNK stress response kinases. Recently we have taken advantage of gadd45a and gadd45b deficient mice to determine the role gadd45a and gadd45b play in the response of bone marrow (BM) cells to genotoxic stress. Myeloid enriched BM cells from gadd45a and gadd45b deficient mice were observed to be more sensitive to ultraviolet radiation (UVC), VP-16 and daunorubicin (DNR) induced apoptosis compared to wild-type (wt) cells. The increased apoptosis in gadd45a and gadd45b deficient cells was evident also by enhanced activation of caspase-3 and PARP cleavage and decreased expression of cIAP-1, Bcl-2, Bcl-xL compared to wt cells. Reintroduction of gadd45 into gadd45 deficient BM cells restored the wt apoptotic phenotype. Both gadd45a and gadd45b deficient BM cells also displayed defective G2/M arrest following exposure to UVC and VP-16, but not to DNR, indicating the existence of different G2/M checkpoints that are either dependent or independent of gadd45. Additional work conducted in this laboratory has shown that in hematopoietic cells exposed to UV radiation gaddd45a and gadd45b cooperate to promote cell survival via two distinct signaling pathways involving activation of the Gadd45a-p38-NF-kB mediated survival pathway and Gadd45b mediated inhibition of the stress response MKK4-JNK pathway (59). These data reveal novel mechanisms that mediate the pro-survival functions of gadd45a and gadd45b in hematopoietic cells following UV irradiation. Taken together, these findings identify gadd45a and gadd45b as anti-apoptotic genes that increase the survival of hematopoietic cells following exposure to UV radiation and certain anticancer drugs. This knowledge should contribute to a greater understanding of the genetic events involved in the pathogenesis of different leukaemias and response of normal and malignant hematopoietic cells to chemo and radiation therapy. These observations set the stage to evaluate, in clinically relevant settings, the impact that the status of gadd45a and gadd45b might have on the efficacy of DNR or VP-16 in killing leukemic cells.